Combining Search-Based and Evolutionary Techniques for Autonomous Pac-Man Gameplay - Muhammad Haramain Asyi Emirryan; Hadisaputro, Jeffrey Matthew; Aditama, Galih Putra; Juwono (Bina Nusantara University, 2025)
Artificial intelligence has become a fundamental component in modern video game development, especially in the creation of autonomous and adaptive non-player character (NPC) behavior. This research proposes a hybrid artificial intelligence approach to enable fully autonomous gameplay in a classic Pac-Man environment without any form of user input. The proposed system combines evolutionary optimization methods with deterministic search algorithms to balance strategic planning and real-time decision-making. A Genetic Algorithm (GA) is utilized to optimize long-term gameplay strategies, including route selection and risk management, while A* pathfinding and adversarial search techniques are applied to support efficient real-time movement and enemy avoidance. Additionally, Breadth-First Search (BFS) and Depth-First Search (DFS) are implemented to model diverse ghost behaviors, resulting in a more dynamic, challenging, and adversarial game environment. Experimental evaluations indicate that the hybrid AI system demonstrates improved navigation stability, longer survival duration, and more consistent pellet collection when compared to baseline artificial intelligence models that rely on single techniques. The results further show that separating strategic optimization from tactical pathfinding enhances overall gameplay performance and adaptability. This study highlights the effectiveness of hybrid AI architectures in game environments and offers a structured educational framework for understanding and implementing artificial intelligence techniques within video game simulations, particularly for classic arcade-style games.